A FRAMEWORK FOR SUPPORT ON GENERATION OF MASSIVE OPEN ONLINE COURSE ADAPTATIVE MOOC USING TECHNIQUES OF CONTEXT ADAPTATION - Junior, Jose Barbosa Dias; Cardoso, Alexandre; Lamounier Junior, Edgard Afonso; Kirner, Claudio (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This paper presents a proposal for a software framework to aid in the development of adaptive MOOC, using techniques adapted to the context. This solution will support the adaptation of the content of MOOCs according to student's profile and preferences. This adaptation is performed in a dynamic way, creating content tailored according to the learning style of each student, generating different materials according to their profile. Aiding in better understanding of the content by the student, allowing the reduction of avoidance of these courses.